THE STRUCTURAL – SEMANTIC ANALYSIS OF THE WORDS RELATED TO “SPORTS” IN TEACHING AND LEARNING PROCESS - Kaljanova, U. (SCIENCE and SOCIETY, 2025)
The article discusses foreign sports terms that are frequently used in the Karakalpak language. Adapted foreign sports terms are used across various branches of sports, and this is supported with multiple examples.
Keywords: denotational; synchronic or diachronic; anthropology and computational semiotics